2022
DOI: 10.3389/fsurg.2022.743274
|View full text |Cite
|
Sign up to set email alerts
|

The Top-Cited Articles With a Focus on Barrett's Esophagus: A Bibliometric Analysis

Abstract: BackgroundBecause the number of published literatures with a focus on Barrett's esophagus (BE) that researchers must be familiar with has quickly increased in recent years, the significance of selective searching and summarization of bibliometrics is also increasing. It is, thus, very important to find a method that can quickly and effectively search the most influential medical science articles. Therefore, the objective of this study was to use bibliometric analysis to assess and characterize the most influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…It has also been reported that the accurate assessment of an article's true impact and popularity requires a period of at least two decades. The highest citation density tends to appear 3–10 years after publication [ 33 ].…”
Section: Limitationsmentioning
confidence: 99%
“…It has also been reported that the accurate assessment of an article's true impact and popularity requires a period of at least two decades. The highest citation density tends to appear 3–10 years after publication [ 33 ].…”
Section: Limitationsmentioning
confidence: 99%
“…Bibliometric analysis provides a quantitative approach to exploring a specific field to discover the dynamics and progress of a discipline (11)(12)(13). A visualized study facilitates the interpretation of data and uncovers the internal connections between them (14).…”
Section: Bibliometric Analysis and Visualized Studymentioning
confidence: 99%
“…There is an urgent need for a statistical approach to summarize the progress of previous research in this field. Bibliometrics is a discipline that uses statistical methods to study the structure and changes and provides a quantitative approach to exploring a particular field to discover the dynamics and progress of a discipline [5,6]. Owing to the fact that Radiomic is a very new discipline, the use of bibliometric tools to evaluate the field has not been learned until now.…”
Section: Introductionmentioning
confidence: 99%